Profile of kidney function markers in patients with COVID-19 hospitalized in the ICU of a hospital in the middle west of Santa Catarina (Research, Society and Development, 2022)
The viral disease called COVID-19, caused by the Sars-Cov-2 virus, had its first records in the city of Wuhan, China, in December 2019. Because it is a disease with respiratory symptoms, a high rate of contagion and gradual worsening, made COVID-19 the biggest pandemic in recent times. The complications of the disease required treatment in Intensive Care Units (ICU) for its most serious victims, which led to a series of events and complications resulting from the junction of the pathology with the consequences of the treatment. This article aims to evaluate, through statistical analysis of medical records and laboratory test reports, the biochemical profile of renal markers in patients hospitalized in the ICU, looking for correlations between the therapy used and the length of stay of these patients. Significant alterations were observed in renal markers, mainly urea, and creatinine, in patients who remained hospitalized for a longer time, concerning the others. Furthermore, all patients were treated with drugs that expressed nephrotoxic characteristics. Finally, a positive correlation between the length of stay of these patients in the ICU, with prolonged exposure to nephrotoxic drugs and kidney damage, can be found.